ANALISA GANGGUAN PEMUTUS TENAGA MESIN CANE CUTTER I - Adib Chumaidy (SINUSOIDA, 2017)
Age-old mill still experiencing demands to improve the quality and oroduction capacity.Repair, renovation, addition of electrical equipment and production machines as supportingproduction should be done. For electrical equipment and machinery are aged beyond safe time limit.One of them : ACB-type circuit breaker point A, imposition of electrical equipment that exceed the timelimit on the plant safe will result in severe, be a disturbance explosion-fire resulting in total failureproduction. Being burdened Cane Cutter machines I which require a large torque because there is avery extreme narrow gap. Than the energy required large power, it takes great energy power,electrical system and installation of electrical equipment must consider regulatory electricity and PUIL2000 or international standards, so that the continuity of safe electric power energy. The use of electricmotor / Cane Cutter I should be considered more in the electrical system, due for chopping sugar cane,then a very large load torque too great and the gap in the extreme, can lead to Locked Rotor. Denganmethod IEC 60 909 in 2000 to calculate the locked rotor current noise ; simplification because thecalculation does not depend on the operating status of ongoing and future load flows. With a series ofanalyzes and short-circuit current using the formula of the total of 3-phase symmetrical fault currentobtained with the largest load disconnection times faster than the time settings. This fault currentDownstream ACB protected and unprotected then the Upstream ACB who do it (ACB point A), thisfault current lead to an explosion / fire in the ACB point A. ACB possible point A has exceeded the timelimit is safe and functioning of protection equipment ACB point A is Electronic or Solid state Trip Unit/ fully adjustable, the fault current exceeds safe limits (Imax overload dan fully adjustabl